Development of Pocketbooks as an Education and Compliance Module for Diabetes Mellitus Patients at the Kaliwungu Health Center, Kudus, Indonesia - Fitriani, Eka; Rina Herowati; Lucia Vita Inandha Dewi (Open Access Indonesian Journal of Medical Reviews, 2023)
Diabetes mellitus (DM) is a chronic disease that requires long-term treatment. Management of DM patients is one of them by providing education. This study aimed to determine the product trial of developing a pocketbook as an educational module using the assessment parameters of experts and DM patients who meet the eligibility criteria at Kaliwungu Health Center, Kudus. This study used qualitative and quantitative analysis. Qualitative analysis in the form of suggestions and input from experts, and quantitative analysis in the form of assessment scores. The method used in this research is research and development. Product development with Borg and Gall procedures. Product trials of pocket book development as a DM patient education module at Kaliwungu Health Center, Kudus, using expert parameters including media experts at 100%, material expert I with a value of 84%, material expert II with a value of 92.3%, material expert III with a value of 100%, expert practitioners with a value of 100% and DM patients with an average value of 80.5% in the category worth using with revision.